Technical Deficiencies and Human Factors in Land Disputes: in the Context of Nepalese Cadastral Surveying - Bhatta, Ganesh Prasad (Journal on Geoinformatics, Nepal, 2006)
in 1964 to support the Land Reform Programme launched by His Majesty’s Government of Nepal. Survey Department looks after these activities from the beginning. The activities are still in practice. The Cadastral Surveying (CS) is the foundation of land administration/management activities in Nepal. Inaccuracies and ineffectiveness in CS activities are the reasons for some of the cases of land disputes that exist in the Nepalese society. The reasons of inaccuracies and ineffectiveness in these activities have been considered in two broader perspectives: technical deficiencies and human factors. The paper is based on a research entitled “Identification of Technical Deficiencies and Human Factors in Land Disputes: in the Context of Nepalese Cadastral Surveying”, which is mainly based on the studies of some of the cases of land disputes, interaction programmes with professionals and field observations, with the focus on identification of technical deficiencies and involvement of human being in various perspectives in the CS activities. Some reasons of possible land disputes because of the CS have been pointed out. SWOT Analysis was performed during the research work to develop guidelines for improvement in the accuracies and effectiveness of the CS activities in the line to mitigate land disputes. Some recommendations have been put forwarded to Survey Department in this regard.